Cruzar el océano: lo que revelan los viajes a España de los mestizos peruanos en la segunda parte del siglo XVI - Alaperrine-Bouyer, Monique (2013)
Using data from the years 1552-1585 in the catalogues of Passengers to America in the General Archive of the Indies in Seville, this article investigates how the metropolitan administration identified and treated Peruvian mestizos returning from Spain, and examines the attitude of the peninsular family toward those born overseas to Spanish fathers and to mothers who were frequently unknown. In other words, the present article seeks to determine what objectives Peruvian mestizos pursued during their stay in the Peninsula and what reception they experienced from the metropolitan administration and from their Spanish families.